P2.001 Performance of the Hologic Gen-Probe APTIMA Assays and PANTHERTM Instrumentation For the Confirmation of Neisseria Gonorrhoeae in Genital and Non-Genital Samples. (13th July 2013) - Lowe, P; Dubedat, S; Turra, M
Abstract : Nucleic Acid Amplification Tests (NAATs) for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) have become routine. These methods are validated for use with urogenital samples and have a faster turn-around-time for results with automation. Testing of non-validated samples is common which raises concerns about assay performance. In Australia, the 2005 Public Health Laboratory Network (PHLN) guideline recommends repeat testing of all initial positive GC NAAT results with a suitable alternate NAAT assay. In this study, results from > 70, 000 patient samples from 2 laboratories were reviewed in accordance with the PHLN recommendations. The laboratories used the APTIMA Combo 2 (AC2) and APTIMA Neisseria gonorrhoeae (AGC) assays with the PANTHER instrument. 72, 253 AC2 results were available for analysis which included 1, 174 (1.68%) initially AC2 reactive (positive or equivocal) samples which also had results for the AGC assay used as the confirmatory assay. For the reactive samples, the agreement between the AC2 and AGC assays occurred in 97.19% of samples; 1135 were positive in both assays and 6 were equivocal in both assays. Sample types tested included those with manufacturer's validation claims; urine, ThinPrep, vaginal, endocervical and urethral swabs and non-validated samples including throat, rectal, eye and joint fluids. Samples from throat swabs showed the highest numbers of discordant results followed by rectal swab samples. The percentage agreement of results obtained from all sample types was excellent, with an overall PPV of > 99%. Without confirmatory testing, false positive results would have been reported for 13 samples representing 0.02% of all samples tested. This study demonstrates that the initial AC2 results can be accepted with high confidence.